Integration of Scouting Methods and Islamic Arts: Realizing the Student Profile of Pancasila Through Geometry Learning - Amanda La Hadi; Selvy Angraeni (FKIP Universitas Halu Oleo, 2024)
This study addresses the challenges of teaching geometry in Indonesian secondary schools by developing innovative instructional materials that integrate Islamic Art and scouting methods. This research adopts an Educational Design Research approach, focusing on the final assessment phase to develop and test geometry learning tools in junior high schools. These tools include modules, teaching materials, and student worksheets that incorporate Islamic Art from local mosques in Kendari City and employ the scouting method, which emphasizes experiential learning and group collaboration. The study demonstrates that integrating Islamic Art and scouting methods enhances students' competencies in alignment with the Profil Pelajar Pancasila (P3) program, which aims to develop character traits such as faith, global diversity, independence, cooperation, critical thinking, and creativity. Field testing in two schools showed that students using these materials achieved high average scores across all P3 indicators, affirming the approach's effectiveness. This research highlights the potential of context-based, culturally relevant instructional materials to improve geometry education and foster essential character traits in students. Future studies should further explore broader applications of these methods to validate their effectiveness in diverse educational settings.